Development of ethanolamine‐based ionic liquid membranes for efficient CO2/CH4 separation. Issue 44 (23rd July 2017) - Ur Rehman, Rashid; Rafiq, Sikander; Muhammad, Nawshad; Khan, Asim Laeeq; Ur Rehman, Asif; TingTing, Liu; Saeed, Muhammad; Jamil, Farrukh; Ghauri, Moinuddin; Gu, Xuehong
ABSTRACT: This study is focused on the development of ionic liquids (ILs) based polymeric membranes for the separation of carbon dioxide (CO2 ) from methane (CH4 ). The advantage of ILs in selective CO2 absorption is that it enhances the CO2 selective separation for the ionic liquid membranes (ILMs). ILMs are developed and characterized with two different ILs using the solution‐casting method. Three different blend compositions of ILs and polysulfone (PSF) are selected for each ILMs 10, 20, and 30 wt %. Effect of the different types of ILs such as triethanolamine formate (TEAF) and triethanolamine acetate (TEAA) are investigated on PSF‐based ILMs. Field emission scanning electron microscopy analysis of the membranes showed reasonable homogeneity between the ILs and PSF. Thermogravimetric analysis showed that by increasing the ILs loading thermal stability of the membranes improved. Mechanical analysis on developed membranes showed that ILs phase reduced the amount of plastic flow of the PSF phase and therefore, fracture takes place at gradually lower strains with increasing ILs content. Gas permeation evaluation was carried out on the developed membranes for CO2 /CH4 separation between 2 bar to 10 bar feed pressure. Results showed that CO2 permeance increases with the addition of ILs 10–30 wt % in ILMs. With 20–30 wt % TEAF‐ILMs and TEAA‐ILMs, the highest selectivity of a CO2 /CH4 53.96 ± 0.3, 37.64 ± 0.2 and CO2 permeance 69.5 ± 0.6, 55.21 ± 0.3 is observed for treated membrane at 2–10 bar. The selectivity using mixed gas test at various CO2 /CH4 compositions shows consistent results with the ideal gas selectivity. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45395. Abstract :